The Crux of Social and Economic Empowerment of Transgender (Hijra) Communities in Bangladesh: A Case Study of Mohammadpur Area in Dhaka (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: hijra; empowerment; social stigma; capacity building; marginalization; social exclusion